Nitrated-, oxygenated- and parent polycyclic aromatic hydrocarbons in organic film on ferries in huangpu river (Shanghai) and source indications of ship-stack emission. (1st February 2023) - Su, Penghao; Zhu, Lihong; Peng, Liming; Tomy, Gregg T.; Yin, Fang; Chen, Lisu; Sun, Dan; Ding, Yongsheng; Li, Yifan; Feng, Daolun
Abstract: Contamination information are desired to fill the gap in the understanding of environmental effects by parent-, nitrated- and oxygenated PAHs (p, n, o-PAHs) from ship stacks. In this study, the organic films on ferries along Huangpu River, one of the busiest inland rivers around the world, were measured seasonally and the compartmental concentrations were rebuilt through a fugacity model to this end. Results revealed that considerable levels of p, n, o-PAHs could be detected in the ferry films. Few seasonal or spatial variations were observed, which indicated a dominant emitter existing in the environments along the river. The compositions of p, n, o-PAHs could be associated with internal combustion engine emissions, however, the composition was different to contamination patterns of on-road traffics. Accordingly, the ship-stack exhausts were suggested to be the primary contributor of p, n, o-PAHs in ferry films. The results of PCA and PMF showed that InP and BghiP could represent the ship-stack PAHs along Huangpu River. Our study highlights a dramatic contribution of ship activities to the contaminations along Huangpu River and provides supports for the usage of organic films on ships as a representative 'sampler' of ship-stack emissions. Graphical abstract: Image 1 Highlights: Measured film-bound p, n, o-PAHs concentrations were presented along Huangpu River. Estimated bulk concentrations showed unobvious spatial and seasonal differences. The contribution of ship was more important than road traffic in ferry surface films. InP and BghiP could delegate the ship-stack PAHs along Huangpu River. The ship-stack nPAHs along Huangpu River was dominated by 6N–BaP, 1N-Pyr.